2021
DOI: 10.1080/23802359.2021.1952119
|View full text |Cite
|
Sign up to set email alerts
|

Current pool of ultimate collection of mitochondrial DNA from remnants of Kalash

Abstract: The mitochondrial DNA (mtDNA) complete control region coverage of 111 individuals from Kalash population of Pakistan has been presented for forensic applications and to infer their genetic parameters. We detected in total 14 different haplotypes with only five unique and nine shared by more than one individual. This population has come up with quite lower haplotype diversity (0.8393) and very higher random match probability (0.1682), and ultimately lower power of discrimination (0.832). Additionally, haplogrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Pakistanis are divided genetically into 11 major distinct groups: Baloch, Brahui, Burusho, Hazara, Kalash, Kashmiri, Makrani, Parsi, Pashtun, Punjabi, and Sindhi [2]. The uniparental marker studies (mtDNA) showed that these ethnic groups share most of their maternal ancestry with South Asians Eurasians East Asians, West Asians, or Sub-Saharan Africans [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Pakistanis are divided genetically into 11 major distinct groups: Baloch, Brahui, Burusho, Hazara, Kalash, Kashmiri, Makrani, Parsi, Pashtun, Punjabi, and Sindhi [2]. The uniparental marker studies (mtDNA) showed that these ethnic groups share most of their maternal ancestry with South Asians Eurasians East Asians, West Asians, or Sub-Saharan Africans [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%